Molotov cocktail protection - protective clothing material for emergency forces - Rahel Krause; Justin Kühn; Thomas Gries; Maren Gültner; Yvette Dietzel (Communications in Development and Assembling of Textile Products)
In order to better protect emergency personnel, a suitable material was sought that would meet various requirements. To achieve this, a project was carried out by the Saxon Textile Research Institute e. V. (STFI), Germany and the Institut für Textiltechnik (ITA) of RWTH Aachen University, Germany, called “Molotov cocktail protection – protective clothing material for emergency forces”. First, suitable fiber mixtures were selected and then tested for a high accuracy of fit. Afterwards, specially designed fabrics were developed and produced to realize a smooth surface. In addition, a coating for high hydrophobia was established. To examine these newly developed fabrics, a test procedure was developed and modified. Results show correlations between fiber selection as well as yarn and fabric construction with the resulting fabric properties. Findings can be given in the form of technological and product-related recommendations.